Achieving high power factor of p-type BiSbTe thermoelectric materials via adjusting hot-pressing temperature. (February 2018) - Wang, Xiaocui; Li, Yuanyue; Liu, Guoxia; Shan, Fukai
Abstract: Achieving high power factor values for BiSbTe alloys is important for further elevation of their thermoelectric performance. In this report, Bi0.4 Sb1.6 Te3 bulk samples were prepared by a fusion method followed by hot pressing at different temperatures (523 K, 573 K, 623 K and 663 K), and their thermoelectric properties were investigated from 300 K to 500 K. It was found that the power factor and thermal conductivity increased significantly with increasing hot-pressing temperature. A record power factor of 53.8 μW/(cm K 2 ) at 300 K was achieved for the sample hot pressed at 663 K. In addition, a maximum ZT of 1.3 at 413 K and average ZT ave of 1.2 at 300–500 K were achieved for the sample hot pressed at 623 K. Highlights: Bi0.4 Sb1.6 Te3 samples were prepared by a fusion method followed by hot pressing. A record PF  = 53.8 μW/(cm K 2 ) was achieved at 300 K for sample hot pressed at 663 K. ZT  = 1.3(413 K) and ZT ave  = 1.2 (300–500 K) were achieved for sample hot pressed at 623 K.